Generalized empirical likelihood-based focused information criterion and model averaging - Naoya Sueishi (Econometrics, 2013)
This paper develops model selection and averaging methods for moment restriction models. We first propose a focused information criterion based on the generalized empirical likelihood estimator. We address the issue of selecting an optimal model, rather than a correct model, for estimating a specific parameter of interest. Then, this study investigates a generalized empirical likelihood-based model averaging estimator that minimizes the asymptotic mean squared error. A simulation study suggests that our averaging estimator can be a useful alternative to existing post-selection estimators.
Keywords: 330; model selection; model averaging; focused information criterion; generalized empirical likelihood